Identity of Salix chingiana (Salicaceae) from China - He, Li; Chen, Shi-Pin (Phytotaxa, 2017)
Chinese authors have in many cases misapplied Salix chingiana K.S. Hao ex C.F. Fang & A.K. Skvortsov to S. rosthornii Seemen. After detailed study of the types, relevant specimens and literature, S. chingiana is synonymized with S. spathulifolia var. glabra C. Wang & C.F. Fang ex T.Y. Ding. In addition, the name S. glandulosa var. stenophylla C. Wang & C.Y. Yu is lectotypified.